2014
DOI: 10.1111/jch.12378
|View full text |Cite
|
Sign up to set email alerts
|

Prehypertension in Rural Northeastern China: Results From the Northeast China Rural Cardiovascular Health Study

Abstract: using a multistage clustering method to select a representative sample of individuals (≥35 years old), resulting in a study population of 11,576 adults. Prehypertension was defined as a systolic blood pressure (BP) in the range of 120 mm Hg to 139 mm Hg and/or a diastolic BP between 80 mm Hg and 89 mm Hg according to the Seventh Report of the Joint National Committee on the Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC 7). The results showed that the meanAEstandard deviation syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…The differences observed in the incidence of prehypertension between different populations might be related to the variation in ethnicity and different population characteristics [ 22 ]. As a result, the reported high incidence of prehypertension in the current study might be attributable to the alarming rise of obesity [ 23 ], increasing trend of diabetes incidence [ 24 ] as the coexistent cardiovascular risk factors with prehypertension [ 25 27 ], high prevalence of low physical activity (40% in a national survey) [ 28 ]and unhealthy diet specifically high amount of dietary salt intake [ 29 ], in Iran. In a study by Khosravi et al on a representative adult population in Isfahan province, it was shown that the amount of urinary excretion of sodium was more than 8 gr/day; hence, it was estimated that the equivalent salt intake was between 9 to 11.8 gr/day [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences observed in the incidence of prehypertension between different populations might be related to the variation in ethnicity and different population characteristics [ 22 ]. As a result, the reported high incidence of prehypertension in the current study might be attributable to the alarming rise of obesity [ 23 ], increasing trend of diabetes incidence [ 24 ] as the coexistent cardiovascular risk factors with prehypertension [ 25 27 ], high prevalence of low physical activity (40% in a national survey) [ 28 ]and unhealthy diet specifically high amount of dietary salt intake [ 29 ], in Iran. In a study by Khosravi et al on a representative adult population in Isfahan province, it was shown that the amount of urinary excretion of sodium was more than 8 gr/day; hence, it was estimated that the equivalent salt intake was between 9 to 11.8 gr/day [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The latest studies have found that the prevalence of CVD in northeast China is much higher than it was in previous years [14][15][16]. Whether this is related to the drinking status of people in this region needs to be further analyzed.…”
Section: Introductionmentioning
confidence: 88%
“…The prevalence and epidemiologic characters of hypertension in China had been thoroughly studied in resent years and reached the conclusion that hypertension became prevalent not only in urban but also in rural areas [ 7 ]. There was high prevalence of hypertension in rural northern, northeastern, and northwestern China; but low level of awareness, and treatment rates.…”
Section: Introductionmentioning
confidence: 99%